1998
DOI: 10.1148/radiology.209.2.9807575
|View full text |Cite
|
Sign up to set email alerts
|

Choledochal cyst with or without biliary atresia in neonates and young infants: US differentiation.

Abstract: US can be helpful in the preoperative differential diagnosis of choledochal cysts in neonates and infants. Cysts are larger, intrahepatic ducts are dilated, and gallbladders are not atretic in patients with CC as compared with those in patients with CCBA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 0 publications
6
45
0
2
Order By: Relevance
“…Kim and associates reported that a choledochal cyst is larger than a CCBA. 24 In this study of infantile extrahepatic biliary tree dilatation, we also found that choledochal cysts had a significantly greater diameter than BDBA. Because there was a high prevalence of BDBA (44%) in infantile biliary tract dilatation in this study, we strongly believe that an operative cholangiogram is indicated for infantile biliary duct dilatation.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Kim and associates reported that a choledochal cyst is larger than a CCBA. 24 In this study of infantile extrahepatic biliary tree dilatation, we also found that choledochal cysts had a significantly greater diameter than BDBA. Because there was a high prevalence of BDBA (44%) in infantile biliary tract dilatation in this study, we strongly believe that an operative cholangiogram is indicated for infantile biliary duct dilatation.…”
Section: Discussionsupporting
confidence: 60%
“…In the same period, we had 187 cases of BA cases, 10.6% with BDBA (19 of 187). BDBA has been reported in the literature under different medical terms, such as choledochal cyst associated with BA, 22 choledochal cyst associated with extrahepatic biliary BA (CCBA), 24 and type I cyst of BA. 25 In the literature, the most common type of BDBA reported is type I cyst, which has been described as a correctable type of BA in the past.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BABC had been reported and had names synonymously as biliary duct dilatation with biliary atresia (BDBA), 13 choledochal cyst associated with extrahepatic biliary atresia (CCBA), 18 and type I cyst of BA.19 A survey by the American Academy of Pediatric Surgery Section found that 13% of patients with cystic dilatation of the CBD had extrahepatic biliary atresia.…”
Section: Differential Diagnosis Of Biliary Dilatation In Childrenmentioning
confidence: 99%
“…Foremost among the differential diagnoses of dilatation of the common bile duct in children is biliary atresia. 40,[55][56][57] In adults, the diagnosis is only sporadically in doubt preoperatively, owing to the quality of modern imaging. Stone impaction with proximal dilatation has been reported to mimic choledochal cysts.…”
Section: Presentationmentioning
confidence: 99%